2015
DOI: 10.1111/1475-4932.12184
|View full text |Cite
|
Sign up to set email alerts
|

Does Living Alone Confer a Higher Risk of Hospitalisation?

Abstract: The rise in one‐person households is a worldwide trend. This means that informal care is less available, particularly for elderly people, with important implications for health‐care utilisation and health expenditure. This paper uses a two‐part model to examine the relationship between living alone and hospitalisations in Australia in terms of both the likelihood and the length of hospitalisation. The results show living alone increases the probability of hospitalisation by 2.9 percentage points and length of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 15 publications
(33 reference statements)
4
20
0
Order By: Relevance
“…; Inouye et al. ; Mu, Kecmanovic, and Hall ; Dolja‐Gore et al. ), and between loneliness and planned and unplanned admissions (Molloy et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Inouye et al. ; Mu, Kecmanovic, and Hall ; Dolja‐Gore et al. ), and between loneliness and planned and unplanned admissions (Molloy et al.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that living alone (Landi et al. ; Mu, Kecmanovic, and Hall ) and being widowed (Dolja‐Gore et al. ) are risk factors for hospital admission, while other studies have found no associations between living alone and hospital admissions (Fernandez‐Olano et al.…”
mentioning
confidence: 99%
“…While some existing studies have shown an association between living alone, or households with only older people, and increased health care utilisation [ 13 17 ], other UK-based studies have not found the same effect [ 18 , 19 ]. However, many of these studies rely on survey data or self-reported utilisation [ 13 15 , 18 , 19 ]; analyse patterns at a practice rather than at an individual patient level [ 16 ]; or focus on only one element of health care services [ 13 , 15 17 ]. The results of existing studies provide conflicting evidence of the impact of living alone on health care utilisation, this study adds to the literature by examining the relationship at a patient level using electronic health records.…”
Section: Introductionmentioning
confidence: 99%
“…21 Living alone is identified as a risk factor for poor self-and mortality in patients with chronic illness 13,22,23 and nursing home admission and hospitalizations in older adults. 24,25 Therefore, the purpose of this study was to examine the potential buffering effect of living arrangements, as an indicator of social support, on the relationship between depressive symptoms and self-care in patients with HF. The specific aim was to determine whether depressive symptoms had direct and/or indirect effects on self-care constructs proposed by Riegel and colleagues (i.e., self-care maintains, self-care management, and self-care confidence) 1,26 in HF patients living alone and those living with others.…”
mentioning
confidence: 99%